Cellular Apoptosis of 4T1 Breast Cancer Cells Induced By V4-UPM Newcastle Disease Virus - Mahadi, Mahani (2007)
This study was carried out to investigate the effects of Newcastle disease virus (NDV) strain V4-UPM in eliminating breast cancer cells through the apoptosis machinery process and the potential use of the virus as an agent for breast cancer therapy. Oncolytic effects of V4-UPM NDV on 4T1, a mouse mammary cancer cell line was investigated via in-vitro and in-vivo assays, and three of the apoptosis characteristic were evaluated through various methods. Propagation of V4-UPM NDV was conducted in the allantoic fluid of 10 day old embryonated chicken eggs after 5 to 7 days incubation. The fluid was harvested, purified, and the haemagglutination (HA) test was carried out to determine the HA titre of the virus. The HA titre obtained from purified V4-UPM NDV was 131 072 or 217. Cytotoxic effects of V4-UPM NDV on 4T1 cell line were first carried out using microculture tetrazolium (MTT) assay to determine the amount required to kill 50% of cancer cells. It was observed that 32 768 or 215 HA unit was required to kill 50% of the 4T1 cells. Further studies were done by observing the morphological changes in treated cells under scanning electron microscope (SEM). The cells treated with V4-UPM NDV showed apoptotic characteristics such as shrinkage and reduction in cell size, cell indention, membrane blebbing and dispersion of cells, compared with oval to round, smooth surface of untreated 4T1 cells. By using confocal microscope, localization of tumor suppressor gene p53 and mitochondria activity in treated cells were evaluated to identify the involvement during the process of apoptosis. Positive localization of p53 in the nucleus of untreated cells was observed after labeling with anti-p53 monoclonal antibody and the localization of p53 outside the nucleus was clearly seen after treatment. V4-UPM NDV is suggested to enhance the function of p53 to cause 4T1 cells to commit suicide. The mitochondrial activity was investigated by using mitotracker red staining and low involvement of mitochondria activity in cancer cells was observed in untreated cells. Greenish fluorescence was observed in treated cells showing higher involvement of mitochondrial activity during apoptosis. Further investigations were carried out based on the in-vitro studies as a preclinical trial on an animal breast cancer model (in-vivo) to evaluate the effects of V4-UPM NDV on cancer tissue. Female inbred Balb/c mice were used as an animal model and induction of cancer was done through inoculation of 4T1 cells into subcutaneous mammary fat pad. After 10 to 14 days, the tumor growth was observed in all induced mice. The statistical analysis of tumor development showed a significant difference (p ≤ 0.05) of tumor volume between control cancer cells and cancer cells treated with V4-UPM NDV. However, no significant changes were observed in body weight and tumor mass. Cell proliferation was significantly reduced as shown by the measurement of apoptotic:mitotic cell via lesion score counted under light microscope. Confirmation of apoptotic cells by specific labeling of DNA fragment with TdT mediated dUTP nick end labeling (TUNEL) assay showed a higher apoptotic percentage counted in cancer cells treated with V4-UPM NDV as compared with cancer control cells. Ultrastructural features of treated tissue were viewed under energy filtered transmission electron microscope (EFTEM) to confirm that cell death due to V4-UPM NDV is via apoptotic pathway. Cells were observed to be tightly connected with other cells, with clear boundaries and with the normal structure of organelles in cancer control cells. The distinct ultrastructural changes prominently seen in 4T1 cells treated with V4-UPM NDV were the apoptotic characteristics, such as, cell shrinkage and resulting spaces in between cells, membrane blebbing, shrunken nucleus and also the presence of numerous numbers of mitochondria and endoplasmic reticulum (ER). From these findings, it was confirmed that the mode of cell death induced by V4-UPM NDV, to eliminate the cancer cells is by apoptosis. This suggested that V4-UPM NDV is a potential agent for breast cancer treatment.